Photo-annealed amorphous titanium oxide for perovskite solar cells. Issue 41 (25th September 2019) - Jeon, Jae Bum; Kim, Byeong Jo; Bang, Gi Joo; Kim, Min-cheol; Lee, Dong Geon; Lee, Jae Myeong; Lee, Minho; han, Hyun Soo; Boschloo, Gerrit; Lee, Sangwook; Jung, Hyun Suk
Abstract : Photo annealing system under dry condition has been developed to fabricate low temperature amorphous TiO2 electron extraction layer for perovskite solar cells. Abstract : Electron selective layers are important to the efficiency, stability and hysteresis of perovskite solar cells. Photo-annealing is a low-cost, roll-to-roll-compatible process that can be applied to the post-treatment fabrication of sol–gel based metal oxide layers. Here, we fabricate an amorphous titanium oxide electron selective layer at a low temperature in a dry atmosphere using a UV light annealing system and compare it with a thermal annealing process. Active oxygen species are created by using UV light to promote hydrolysis and condense the TiO2 precursor, which removes organic ligands effectively. The photo-annealed TiO2 -based perovskite solar cell has a power conversion efficiency of 19.37% without hysteresis.